Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5812/archcid.12673
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Brucella spp. in Dairy Products by Real-Time PCR

Abstract: Background and Objectives: Brucella is an intracellular gram-negative bacterium that can infect many kinds of mammals like humans, sheep, cattle, etc. Brucellosis is a contagious occupational disease caused by Brucella spp. that affects individuals who have close contact with infected animals. The clinical features of Brucellosis are not disease-specific and almost every organ can be affected. This zoonotic disease is a great health concern and economically important in many countries, such as Iran. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…These findings are harmonious with published similar studies from Pakistan (14), Iraq (10,13,15), and India (16). On the other hand, higher rates of anti-Brucella antibodies were documented in studies in Libya 21% (17), India 27% (18), Egypt 36.4%-56.2% (19), and Iran 45% (20). Such variations might be attributed to various factors including the extent of encounters with wildlife (natural reservoirs), seasonality, level of available veterinary care, and testing methodology (10,13).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are harmonious with published similar studies from Pakistan (14), Iraq (10,13,15), and India (16). On the other hand, higher rates of anti-Brucella antibodies were documented in studies in Libya 21% (17), India 27% (18), Egypt 36.4%-56.2% (19), and Iran 45% (20). Such variations might be attributed to various factors including the extent of encounters with wildlife (natural reservoirs), seasonality, level of available veterinary care, and testing methodology (10,13).…”
Section: Discussionsupporting
confidence: 83%
“…A Nigerian study also detected a similar prevalence in livestock by the bacteriological approach (21). Besides, different rates of Brucella contaminating sheep and goats' raw milk were found in Iran ranged from 1.2% to 45.5% (20,22). In addition to seasonal and epidemiological variations in different regions, isolation of Brucella is also influenced by the bacteriological protocol.…”
Section: Discussionmentioning
confidence: 83%
“…The analytical detection limit of the qPCR based on this target ranged from 1 to 6 genome copy/g in cheese [ 17 ]. Previous studies in India and Iran using PCR and quantitative real-time PCR showed high contamination rates in raw goat milk (88.8% and 45.5%, respectively) [ 18 , 19 ]. While using the milk ring test or ELISA, the contamination rates in cow′s milk ranged between 4.4 to 5.8% in India [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Brucella reservoirs still exist in the wild [16,92]. Te recent studies conducted in India, Iran, and Qatar using PCR techniques have confrmed the presence of Brucella species in milk and other dairy products [18,55,66]. Tis is a signifcant concern as humans can contract Brucella infection by consuming contaminated milk (Table 1).…”
Section: Brucella Prevalence In Milk and Various Dairy Productsmentioning
confidence: 99%